Pengaruh Persepsi Wajib Pajak Orang Pribadi Atas Sanksi Perpajakan Dan Kualitas Pelayanan Pajak Terhadap Kepatuhan Perpajakan - Nancy Marchelly; Waluyo Waluyo (Universitas Multimedia Nusantara, 2012)
Tax Revenue is one of the most important sources of revenue for making the state expenditure budget (APBN). As a revenue dominant source for APBN derived from tax sector. The main objective of this study is to analyze the effect of tax sanctions and tax service quality on individual tax compliance. This study focus on individual entrepreneurs tax payer those registered at the Primary Tax Office Tigaraksa (KPP Pratama Tigaraksa) especially in Gading Serpong Tangerang. Samples were selected by convenience sampling method, the data used in this study is primary data. The results show indicate (1) tax sanction has significantly affect to individual tax compliance, (2) tax service quality has significantly affect to individual tax compliance, (3) tax sanction and tax service quality have significantly affect to individual tax compliance. Keywords: Tax penalty, tax service quality, individual tax compliance